Legal Protection for Victims of Narcotics Misuse under Law No. 35 of 2009 - rini siboro; Nurmaya R.A Simanjuntak2 (Veteran Law Review, 2025)
Drug abuse is one of the serious issues faced by the Indonesian nation, including the North Sumatra region. The distribution and misuse of narcotics have increasingly spread across all levels of society and resulted in numerous victims. This study aims to examine the extent of legal protection for victims of drug abuse and to evaluate the role of the North Sumatra Provincial National Narcotics Agency (BNNP SUMUT) in carrying out its duties and functions. The research method used is empirical juridical, which views law as a real behavior in society and observes its implementation directly at the BNNP SUMUT office. The results of the study indicate that drug users are victims of crimes committed by drug trafficking syndicates. Therefore, drug addicts require special treatment in the form of rehabilitation and legal protection to enable them to recover and contribute again as responsible citizens. BNNP SUMUT holds a key role in prevention, community empowerment, rehabilitation, eradication of illicit drug networks, and cross-sectoral collaboration at the local level. This study suggests that BNNP SUMUT should further strengthen synergy and coordination with law enforcement agencies and increase active public participation.